Remote control using telephone / Ahmed Azad Ismail and Wan Nor Rashidi Wan Tajuddin - Ismail, Ahmed Azad; Wan Tajuddin, Wan Nor Rashidi (2004)
Remote control using telephone is a control system connected to desired appliance and acts as a switch. However this remote control limits its number of appliance to be connected to it. In this report, a new method of making use of the telephone is discovered. It uses the signal from the telephone line and the telephone keypad as its interface with the appliance. The purpose of this project is to enhance the use of telephone rather then use it as a communication tool.